Supersymmetry in mathematics and physics UCLA Los Angeles, USA 2010 - Ferrara, Sergio; Fioresi, Rita; Varadarajan, V.S (Lecture notes in mathematics, 2011)
Supersymmetry was created by the physicists in the 1970's to give a unified treatment of fermions and bosons, the basic constituents of matter. Since then its mathematical structure has been recognized as that of a new development in geometry, and mathematicians have busied themselves with exploring this aspect. This volume collects recent advances in this field, both from a physical and a mathematical point of view, with an accent on a rigorous treatment of the various questions raised.